In Situ Measurement and Remediation of Condensation Issue in Sarawak General Hospital Molecular Lab During COVID 19 - Muhammad Syukri Imran, Abdullah; Azhaili, Baharun; Abdul Malik, Zainal Abidin; Noor Muhammad, Abdul Rahman; Nyuk, Yen Chin (Springer Nature Singapore Pte Ltd, 2023)
Sarawak General Hospital Molecular laboratory suffers significant condensation issues particularly above its ceiling due to combination of design and construction shortfall. Overcooling of laboratory and inappropriate selection of insulation were found to be the major contributing factor. The solution was to introduce 50 mm Expanded Polystyrene (EPS) layer as a thermal barrier within the ceiling layers. Two units of dehumidifier with a total capacity of 70L/day were installed at attic level to control humidity to 60%. The corrective measures have been able to reduce the condensation risk greatly by increasing the difference between air dew point and surface temperature of ceiling by 6.7 °C. In general, the rectification work selected was able to minimize the laboratory downtime using a sustainable, environmental and budget friendly material